Instruksi Pendidikan Agama Kristen Dalam Mengembangkan Karakter dan Nilai-Nilai Spiritual dalam Era Digital 5.0 - Zebua, Sri Iman Putri; Giban, Yoel; Karlau, Sensius Amon (EDULEAD: Journal of Christian Education and Leadership, 2024)
In this technological era, many changes have occurred in everyday life, including Christian religious education. In situations like this, Christian religious education instruction plays a crucial role in building strong student characters and spiritual values relevant to the current situation. Christian religious education instruction in the current digital era pays attention to specific features of technology usage. Firstly, Christian religious education institutions have the ability to adapt to technological advancements and utilize them to effectively and efficiently deliver religious messages through the use of digital platforms and social media to build online communities and serve as references for sharing religious teachings. Christian religious education emphasizes the formation of strong character. Students are encouraged to be honest, responsible, and faithful in using technology in this challenging digital era. Christian religious education can develop spiritual values relevant to technological advancements, such as responsible usage, honesty in sharing information, and privacy protection. This includes the ability to use technology in a healthy manner, such as avoiding excessive dependency and controlling usage time. It is crucial for students to understand how to apply these principles in online interactions and use technology for their own and others' well-being. The researcher will discuss "Christian Religious Education Instruction in Developing Character and Spiritual Values in the Digital Era 5.0" using descriptive qualitative research methods. The researcher will use literature research to reinforce the writer's archives.AbstrakPada periode teknologi ini, banyak perubahan telah terjadi dalam kehidupan sehari-hari, termasuk pendidikan agama Kristen. Dalam situasi seperti ini, instruksi pendidikan agama Kristen memainkan peran penting dalam membangun karakter siswa yang kuat dan nilai-nilai spiritual yang relevan dengan situasi saat ini. Instruksi pendidikan agama Kristen dalam era digital saat ini memperhatikan fitur tertentu dari penggunaan teknologi. Pertama, lembaga pendidikan agama Kristen memiliki kemampuan untuk menyesuaikan diri dengan kemajuan teknologi dan memanfaatkannya untuk menyampaikan pesan agama secara efektif dan efisien melalui penggunaan platform digital dan media sosial untuk membangun komunitas online dan menjadi rujukan dari berbagi pengajaran agama. Pendidikan agama Kristen menekankan pembentukan karakter yang kokoh. Siswa didorong untuk menjadi jujur, bertanggung jawab, dan setia dalam menggunakan teknologi di era digital yang penuh tantangan ini. Pendidikan agama Kristen dapat mengembangkan nilai-nilai spiritual yang relevan dengan kemajuan teknologi, seperti penggunaan yang bertanggung jawab, kejujuran dalam berbagi informasi, dan perlindungan privasi. Ini mencakup kemampuan untuk menggunakan teknologi dengan cara yang sehat, misalnya menghindari ketergantungan yang berlebihan dan mengontrol waktu. Sangat penting bagi siswa untuk memahami cara menerapkan prinsip-prinsip ini dalam berinteraksi secara online dan menggunakan teknologi untuk kebaikan diri mereka sendiri dan orang lain. Peneliti akan membahas "Instruksi Pendidikan Agama Kristen Dalam Mengembangkan Karakter dan Nilai-Nilai Spiritual dalam Era Digital 5.0" dengan menggunakan metode penelitian kualitatif deskriptif. Peneliti akan menggunakan penelitian kepustakaan untuk memperkuat arsip penulis.